The Montessori Pedagogy: A Multi-Sensory Approach to Childhood Education - Ogbemudia, Ifeoma M.; Alasa, Victor Mafone; Ikenyiri, Joseph C. (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Montessori is an activity-oriented, self-directed, age-appropriate, fun, and hands-on learning method. It is an educational approach in which children make creative choices in their learning, discover things for themselves, and are productive workers. At the same time, the classroom teachers offer appropriate guides to the children in the learning process as facilitators of learning. This educational method facilitates children's creative abilities and self-expression, making learning permanent. This is because Maria Montessori believed that education should prepare children for all-around development (physically, mentally, emotionally, and socially) by allowing them to engage in age-appropriate activities and skills and passionately explore the rich learning environment independently based on their background and mental abilities. These will help them satisfy their developmental and learning needs, thereby promoting their natural growth and learning.